1996
DOI: 10.1177/107602969600200408
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Proteins of Hemostasis in the Hepatointestinal Form of Schistosomiasis Mansoni

Abstract: The hepatosplenic form of schistosomiasis mansoni is associated with impairment of blood coagulation, a result of reduced synthesis of clotting factors and inhibitors, enhanced fibrinolytic activity, or "consumption" of plasma clotting proteins. The pathogenesis of the latter mechanism has not been elucidated. Schistosoma mansoni (Sm) has a long lifespan as an intravascular fluke, probably a consequence of its ability to evade host immunologic defense mechanisms. In order to determine if the parasite is able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…No Brasil, calcula-se que o número de pessoas infectadas pelo S. mansoni seja de aproximadamente 10 milhões. O parasita escapa de mecanismos iniciais de defesa orgânica (6) e 90% a 95% das pessoas infectadas evoluem para formas crônicas da doença com manifestações hepáticas. As alterações hepáticas constituem as mais importantes manifestações da doença, sendo característico o quadro anatomopatológico da fibrose de Symmers.…”
Section: Introductionunclassified
“…No Brasil, calcula-se que o número de pessoas infectadas pelo S. mansoni seja de aproximadamente 10 milhões. O parasita escapa de mecanismos iniciais de defesa orgânica (6) e 90% a 95% das pessoas infectadas evoluem para formas crônicas da doença com manifestações hepáticas. As alterações hepáticas constituem as mais importantes manifestações da doença, sendo característico o quadro anatomopatológico da fibrose de Symmers.…”
Section: Introductionunclassified
“…For the form without portal hypertension, lesion markers and hepatic function are within normal limits. Patients with portal hypertension are characterized by the extent of preservation of hepatic function in relation to the degree of portal hypertension, although some laboratory alterations have been found that characterize organ dysfunction from an early stage [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%